DETERMINAN AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DENGAN PERILAKU PEMIMPIN SEBAGAI VARIABEL MODERASI (STUDI KASUS PADA KECAMATAN BINJAI KABUPATEN LANGKAT) - Khan, Silvia Frastika; Junita, Afrah; Azhar, Iqlima (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the accountability determinants of village fund allocation management with leader behavior as a moderating variable. This research was conducted in Binjai District, Langkat Regency. The sampling technique used was a saturated sample with a total sample of 54 respondents. The data collection method used a questionnaire with a Likert scale. The data analysis method used in this study is multiple linear regression and moderated regression analysis using a significant level of 0.05. The results showed that partially, the use of the SISKEUDES application, village apparatus competence, and leader behavior had a significant positive effect on the accountability of village fund allocation management. Moderation regression analysis shows that the leader behavior variable strengthens the relationship between the effect of using the SISKEUDES application on village fund allocation management accountability and the leader behavior variable weakens the relationship between the influence of village apparatus competence on village fund allocation management accountability. The value of the coefficient of determination (R2) is 55.1 percent.